Coupling between oxygen redox and cation migration explains unusual electrochemistry in lithium-rich layered oxides - William E. Gent (Nature Portfolio, 2017)
Lithium ion battery electrodes employing anion redox exhibit high energy densities but suffer from poor cyclability. Here the authors reveal that the voltage of anion redox is strongly affected by structural changes that occur during battery cycling, explaining its unique electrochemical properties.